44 Dynamic Tumor Tracking with SBRT dedicated system VERO (Brainlab): Quality control and PTV volume reduction. (December 2018) - Jimenez, G.; Mazurier, J.; Marre, D.; Mathy, N.; Zarate, D.; Camilleri, J.; Gallocher, O.; Pinel, B.; Chevelle, C.; Franck, D.; Latorzeff, I.
Abstract : Introduction: SBRT for mobile tumors requires a breathing control method. Since 2014, the dedicated SBRT system VERO (Brainlab-Mitsubishi) provides a real-time dynamic tracking method: "dynamic tracking" (DT). We present this method and the results obtained for quality control, PTV volume and treatment time reduction. Methods: The robotic irradiation head of the VERO system (6 MV) is equipped with a 5 mm MLC and follows in real time the target position, thanks to gyroscopic movements guided by infrared and radiological control. DT method was used for liver and pancreas (41 and 3 patients) and thoracic lesions (60 patients) for which the movement amplitude, evaluated by 4DCT (RPM Varian), was >7 mm and after marker implantation (Visicoil, IBA). The treatment plan (TPS IPLAN, Brainlab) was performed with 6 to 8 non-coplanar beams and the Monte Carlo algorithm for lungs on the exhale phase. PTV Margins were determined with the Van Herk et al. 2000 method. PT V DT volume (using DT) was compared to PT V ITV (calculated with MIP images for Internal Target Volume, ITV method) for 60 patients. Treatment times were evaluated for each session for 104 patients. DT mechanical and dosimetric accuracy were evaluated with QUASAR Respiratory Motion et CIRS 008A dynamic thorax phantoms, EBT3 films associated to Doselab Pro software, and with log files analysis. Quality control for 104 patients was performed with Brainlab mobile platform and calibrated films. Results: PTV margins are 5 mm for lung and 8 mm for liver. The mean PT V DT was 28.8 cc (6.5 to 14.3 cc) and 46.4 cc for PT V ITV (10.4 to 139 cc), so a 40% volume reduction. The mean treatment time for DT was 25 min, lower than the one for ITV method for which control CBCT are necessary. The patient breathing rates (frequency and amplitude) are often irregular during treatment and different from the reference 4DCT. This doesn't affect the treatment delivery and target tracking. With 4 year a follow-up, the clinical tolerance during and after SBRT with DT is very good with 1 case of symptomatic grade 3 radiation pneumonitis (PR) and 8 asymptomatic PR for 60 patients. The DT mecanical accuracy was measured <0.7 mm and the dosimetric accuracy <1 mm. The patient QC with films has showed an agreement between calculation and measurement for 95% patients with 95% des points with γ < 1 (3%-1 mm). Conclusion: DT allows treatments with breathing control for all patients, even those with irregular breathing rates. Treatment times are lower than classical treatments based on ITV with an accuracy <1 mm and a PTV volume reduction of 40%.